1997
DOI: 10.1093/ptj/77.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Impairment and Physical Performance Measures for Persons With Parkinson's Disease

Abstract: The results suggest that in the early and middle stages of PD, many of the measures of impairment and physical performance are relatively stable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
95
1
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(102 citation statements)
references
References 15 publications
5
95
1
1
Order By: Relevance
“…25,28,34 The patients in this study also walked more slowly in the Ten Meter Walk Test, where the average time taken to complete the test was between 10-11sec, compared to 8.8sec previously reported reported in the study by Schenkman et al 28 This may be due to differences in disease severity, however this is difficult to assess, as data pertaining to disease stage was not available for analysis in the current study. Balance is one of many elements that may contribute to walking performance in PD.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…25,28,34 The patients in this study also walked more slowly in the Ten Meter Walk Test, where the average time taken to complete the test was between 10-11sec, compared to 8.8sec previously reported reported in the study by Schenkman et al 28 This may be due to differences in disease severity, however this is difficult to assess, as data pertaining to disease stage was not available for analysis in the current study. Balance is one of many elements that may contribute to walking performance in PD.…”
Section: Discussioncontrasting
confidence: 49%
“…These tools have been previously validated to assess balance, 13,19,20,24 and walking performance 25,26 and their utility has been demonstrated in patients with PD. 10,21,[23][24][25]27,28 The patient's demographics, PD history and falls history were also documented collected from patients and their medical charts. Statistical analysis was undertaken in This information was collected for all patients who met the study criteria by undertaking a retrospective chart analysis and entering the data into a Microsoft Excel spreadsheet.…”
Section: All Identified Patients Referred To the Outpatient Rehabilitmentioning
confidence: 99%
“…For each subject, the mean of the 3 trials was obtained for the spatiotemporal data. In other studies, 15,16 good repeatability of 3 trials of normal walking has been reported. The selected kinematic and kinetic gait parameters used in the analyses were determined on the routine protocol of the gait analysis laboratory of the Pellenberg University Hospital, Leuven, Belgium.…”
Section: Instrumentation and Proceduresmentioning
confidence: 62%
“…Few studies reported walking capacity during the 6MWT in people with PD 8,27,28 . Our results demonstrated that those patients who were able to walk shorter distances also had a worse perception of their QoL.…”
Section: Discussionmentioning
confidence: 99%